(untitled) (Fiep Bulletin - online, 2015)
This article presents a study on the culture of movement and points a theoretical-practical proposal of interest to the promotion of citizenship through the contents of physical education School, based on Pedagogy Critical Liberator proposed by Eleanor Kunz. The overall objective of the research is addressing the culture of movement and its contents as a mediator between practice and reflection, to promote an individual socially participatory. Specifically, will be defend such contents in physical education classes as a way to understand the importance of social and political participation in the defense of their rights, in the exercise of their duties and adopting attitudes of solidarity, cooperation and respect for the construction of a better world. The methodology of this article arises as a documental analysis of records about development, philosophy, sociology, pedagogy and educational policies of the sport. This work is justified in providing physical education teachers, a guidance to develop the set of content that encompass the culture of movement, to meet national education policies, for the formation of an individual and participatory.